Rancang Bangun Sistem Informasi Desa Manulondo Berbasis Web - Maria Yuniarti Nggewa; Ferdinandus Lidang Witi (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2021)
This research aimsto produce a village web-based information system design in Manulondo Village. This application contains the design of a village information system including village profiles, population information, and village potential information. This research uses the method waterfall. The research stages include data collection, analysis, design, coding, implementation testing. The trial using BlackBox Testing. That is by testing the user interface system to find out whether the user interface contained in this application can function properly as expected. That results of the software design in the form of a web-based Manulondo Village information system, consist of, serach for population information an village potential information.